Assessing methods for effect-driven design: Evaluation of a social design method. (March 2016) - Tromp, Nynke; Hekkert, Paul
Abstract : The study reported in this paper describes the evaluation of the Social Implication Design (SID) method. This effect-driven design method aims to support designers in designing the influence of design manifestations on behaviour in order to counteract social issues. To study the effectiveness of the method, both a multiple-case study with designers and a narrative-based study with social experts have been executed. Based on our findings we discuss the strengths and weaknesses of the method, and suggest improvements. We conclude this paper by reflecting on our approach as research methodology for assessing effect-driven design methods and argue that qualitative studies, prior to validating design methods quantitatively, will increase the significance of design methodology for design practice. Highlights: A method to realize social impact through design is evaluated in a multiple-case study. By means of a narrative-based study with experts, we assessed the quality of the design outcomes. We discuss both studies as research methodology to assess effect-driven design methods. Qualitative assessments of methods help improving their fit with design practice.